Debt Overhang, Debt Reduction and Investment : The Case of the Philippines. (IMF Working Papers; Working Paper, 1990)
While there is a substantial body of literature on the effects of 'debt overhang' on investment in heavily-indebted countries, there is surprisingly little empirical work available on this subject. This paper tests the hypothesis that the stock of foreign debt acts as a disincentive to private investment in the specific case of the Philippines. The empirical estimates provide support for this hypothesis, particularly after 1982. The estimates indicate that a USD 1.3 billion debt reduction (such as the one completed through the buyback operation in early 1990) would increase investment demand by something between one half and two percentage points of GNP.